PENGARUH MEDIA EDUKASI VIDEO ANIMASI TERHADAP PENGETAHUAN CERDIK UNTUK MENCEGAH DIABETES MELITUS PADA REMAJA - Azmii, Alfiyyah Nurul; Ruhmawati, Tati (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes Mellitus, also known as "The Silent Killer," is one of the chronic non-communicable diseases. There was a drastic increase in the number of child diabetes cases in Indonesia in January 2023, totaling 1,645 patients. The rise in childhood diabetes is associated with poor lifestyle habits and obesity, which are the highest risk factors for diabetes in children. Objective: To enhance students' knowledge about CERDIK to prevent Diabetes Mellitus at SMAN 15 Bandung. Methods: This study employed a mixed-method approach with a sequential exploratory design. The research subjects were 80 tenth-grade students selected through purposive sampling. Knowledge data were collected using questionnaires and interviews, then analyzed using the Wilcoxon test. Results: The study results showed an increase in students' knowledge scores by 80 points. Based on the analysis test, a significant value of 0.000 was obtained for knowledge, indicating <0.05. Conclusion: There is an influence of animated video education on CERDIK knowledge to prevent diabetes mellitus among students. Recommendations: Add variations in evaluation methods and expand research to different age groups and backgrounds to ensure the generalization of findings and explore the long-term impact of using animated videos as a health education medium.